A visibilidade dos desastres naturais (enchentes e inundações) de Mato Grosso e Cuiabá, no âmbito dos bancos de dados global, regional e local - Araújo, Míria Brandão de (2018)
Natural disasters are characterized by adverse events that cause major impacts on society, these events can be differentiated according to their origin and still caused by the impact of each natural phenomenon, where their intensity over a particular area or populated region, may or may not be aggravated anthropogenic activities. In this dissertation an analysis was made of how the spatial configuration in the urban environment is a manifestation of social and historical processes, is closely linked to the occurrence of disasters, which in conceptual terms refers to the combination of two elements: susceptibility and vulnerability. The objective of the research was to analyze the occurrence of natural disasters in Brazil, Mato Grosso and Cuiabá and the visibility of these events in the Data Banks in the global, regional and local scales. The databases analyzed and analyzed were the EM-DAT - Emergency Events Database, Sigma - Swiss Reinsurance Company, Glide - Global Disaster Identifier Number, NatCAT Munich Reinsurance Company, at the regional and local scale are presented the Brazilian Disaster Yearbooks Natural Disasters (2012 and 2013), S2ID - Integrated Disaster Information System, the Brazilian Atlas of Natural Disasters and the Deputy Secretariat for Civil Protection and Defense (SAPDEC-MT) that provide information on natural disasters occurring in these scales of approach. The purpose of studying each database is essential, since each one has registers, information bases and diversified acknowledgments, with the purpose of bringing this concrete, truthful and useful information to the competent bodies, aiding in the decision making with the affected population . The present dissertation was based on a bibliographical and documentary survey of data provided by international, regional and local databases. The results found in the present dissertation show that in the world in recent years several countries among them: China, the United States, India, the Philippines and Indonesia were the hardest hit by natural disasters. The average number of deaths in the last decade was 76,400 people. The reduction of events and impacts such as floods focused on the implementation of prevention measures carried out by several affected countries, which reduced the damage to the population. The database that has a 117-year time frame of recorded data is EM-DAT, a database that receives information from several sources and uses criteria to support the collected data. The analyzed databases presented similar results, but exposed in different ways, which generates discrepancies between them. For Brazil, the southeast region presents the highest number of occurrences of hydrological events already registered. In the state of Mato Grosso some municipalities present recurrence of events such as floods and floods, mostly present in river banks, which is not different in the studied capital, Cuiabá. Through the research it was found that it was always from the river banks that the highest level of flooding occurred, as well as the floods of 1942, 1974, 2001 and 2005.